The Development of Facility Database for FKAAB Building Using GIS Application - Idris, NURUL ELFIRA SALAMAH BINTI MD IDRIS; Mustaffa A.A., (Recent Trends in Civil Engineering and Built Environment, 2022)
There is a web application called as Geographic Information System (GIS) was designed to overcome the problem on the lack of data information about the location of building and facilities. The Development of database for FKAAB building is the way to overcome the hard time that FKAAB occupants having to orientate themselves and find the exact locations that they want. The method on developing the system consist of two phases which is phase 1 (database design) and phase 2 (database development). Several software was used in developing the system which is Excel for collecting data, AutoCAD for editing the drawing and QGIS form developing the database. This research will more focus on the laboratories inside the FKAAB building to solve the problem that student especially for newly student and visitors with the information provided such as “JABATAN”, “KLUSTER”, name of laboratory, No. Bilik, Name of lab assistant, Phone and office number, email and also picture for make the users easily make a finding of the laboratory. From the finding, by developing the Database of Laboratory for FKAAB building will help occupant for making a finding in a short time, with the direction given and also information needed were provided in this system. Other than that it will help the occupant make a finding in easiest way because this database will consist of image of the laboratory that make the occupant can imagine where the laboratory were located. As a result, this system was really useful for FKAAB in order facing the digital lab management.